Impact Of Return On Asset, Current Ratio And Debt To Equity Ration On Price With BI Rate As Moderation Variable In Mining Company - Wico Jontarudi Tarigan; Mahaitin H Sinaga; Sri Martina (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2024)
The study analyzes empirically the impact of Return on Asset (ROA), Current Ratio (CR), and Debt to Equity Ratio on the stock price with BI Rate as a moderation variable. This study analyzes the impact of Return On Asset, Current Ratio and Debt To Equity Ratio on the stock price and measures the effect of BI Rate as a moderation variable on the relationship between ROA, current ratio, DER and stock price. The research period is from 2019 – 2021 with a sample population of 20 companies in the mining sector listed on the Indonesian Stock Exchange. Data analysis using double linear regression methods, F test and T test. And to test moderation variables using residual test. The results of the research revealed that simultaneously ROA, QR, DER had a significant influence on the stock price, but partially ROA variables had a positive effect on the share price while CR and DER did not have an impact on the price of the stock and BI Rate did not moderate the relationship between ROA, CR, and DER with the stock prices